Giant moving vortex mass in thick magnetic nanodots - Guslienko, K. Y. (Sci Rep, 2015)
Magnetic vortex is one of the simplest topologically non-trivial textures in condensed matter physics. It is the ground state of submicron magnetic elements (dots) of different shapes: cylindrical, square etc. So far, the vast majority of the vortex dynamics studies were focused on thin dots with thickness 5–50 nm and only uniform across the thickness vortex excitation modes were observed. Here we explore the fundamental vortex mode in relatively thick (50–100 nm) dots using broadband ferromagnetic resonance and show that dimensionality increase leads to qualitatively new excitation spectra. We demonstrate that the fundamental mode frequency cannot be explained without introducing a giant vortex mass, which is a result of the vortex distortion due to interaction with spin waves. The vortex mass depends on the system geometry and is non-local because of important role of the dipolar interaction. The mass is rather small for thin dots. However, its importance increases drastically with the dot thickness increasing.